Enhancing Growth, Yield, and Physio-Chemical Properties of Mustard (Brassica Napus L) Through Combined Application of Organic and Inorganic Fertilizers Under Salinity Condition in Satkhira, Bangladesh (SAARC Journal of Agriculture, 2023)
A field experiment was carried out to evaluate the combined application of organic and inorganic fertilizers on growth, yield, and physio-chemical properties of mustard (Brassica napus L) during the Rabi season 2021-2022 at the experimental field of BINA (Bangladesh Institute of Nuclear Agriculture) substation farm, Satkhira, Bangladesh. The experiment had 10 treatments viz. T1 = 100% RDF (Recommended Dose Fertilizer), T2 = 75% RDF + 3 ton ha-1 vermicompost, T3 = 50% RDF + 5 ton ha-1 vermicompost, T4 = 75% RDF + 3 ton ha-1 cow-dung, T5 = 50% RDF + 5 ton ha-1 cow-dung, T6 = control, T7 = 3 ton ha-1 cow-dung, T8 = 5 ton ha-1 cow-dung, T9 = 3 ton ha-1 vermicompost, T10 = 5 ton ha-1 vermicompost with three (3) replications in randomized complete block design (RCBD). The combined effect of treatments varied significantly for most of the characters studies. The results revealed that the maximum plant height (cm), No. of primary branches plant-1, no. of secondary branches plant-1, total siliqua plant-1, siliqua length (cm), seeds siliqua-1, seeds plant-1, and yield plot-1 were recorded with the application of 75% RDF + 3 ton ha-1 vermicompost which was significant over control. The combined effect of organic and inorganic fertilizers was found significant in the growth, yield, and physio-chemical properties of mustard cultivation. SAARC J. Agric., 21(2): 169-182 (2023)